Genomic Characterization of a Uropathogenic Escherichia coli ST405 Isolate Harboring blaCTX-M-15-Encoding IncFIA-FIB Plasmid, blaCTX-M-24-Encoding IncI1 Plasmid, and Phage-Like Plasmid - Yao, Mianzhi; Zhu, Qianhui; Zou, Jin; Shenkutie, Abebe Mekuria; Hu, Songnian; Qu, Jiuxin; He, Zilong; Leung, Polly H. M. (Frontiers in Microbiology, 2022)
Escherichia coli sequence type 405 is an emerging antibiotic-resistant clonal group associated with global dissemination of extended-spectrum β-lactamase-producing E. coli. In this study, we firstly report the assembly and characterization of an uropathogenic E. coli ST405 genome, SZESBLEC201, based on long reads and short reads obtained from Nanopore and Illumina sequencing platforms, respectively. Whole-genome sequencing revealed that SZESBLEC201 harbored a 5,020,403-bp chromosome and three plasmids：namely, pSZESBLEC201-1, pSZESBLEC201-2 and pSZESBLEC201-3. Plasmid pSZESBLEC201-1 (111,621 bp) belonged to IncFIA-FIB type and harbored blaCTX-M-15. However, the conjugative transfer-associated genes were missing in pSZESBLEC201-1 rendering this plasmid not conjugatively transferable. pSZESBLEC201-2 (95,138 bp) belonged to phage-like plasmid, which showed strong genome synteny with E. coli phage P1 but absence of mobile genetic elements and a number of regulatory genes. pSZESBLEC201-3 (92,865 bp) belonged to IncI1 type and carried blaCTX-M-24. In contrast to pSZESBLEC201-1, pSZESBLEC201-3 was shown to retain its full active conjugation machinery and was shown to be transferred by conjugation. Genetic features of the genome showed that the strain has a unique virulence pattern in comparison with its genetically similar strains in the same country. The plasmid backbones exhibited a high degree of similarity to those of geographically distant isolates, highlighting the globally spread of blaCTX-M genes and the genome plasticity of this clonal group. The co-existence of two blaCTX-M variants in the same strain poses an increased risk for emergence of new blaCTX-M variants. Further studies on phage-like plasmids are necessary for providing insights into their biological activities and clinical significances.